Canons of Proportion and the Laws of Nature: Observations on a Permanent and Unresolved Conflict. Issue 1 (20th June 2014) - Curti, Mario
Abstract : The mind of the artist always seems to oscillate between two poles: on one side, reality as represented by nature in all its aspects, and on the other, the dream of absolute perfection. This is the fundamental problem of the eternal conflict between the laws of nature and the canon of aesthetic proportions, which presents itself in different, though often related, guises. This article identifies, through explorations of thinkers from Vitruvius, to Galileo, to Le Corbusier, the problematic knots of a phenomenon that the champions of ideal proportions have always had to face and often to hide, even from themselves, when confronted with the evidence of facts.